Estradiol and Testosterone Secretion by Human, Simian, and Canine Testes, in Males with Hypogonadism and in Male Pseudohermaphrodites with the Feminizing Testes Syndrome - Kelch, R. P. (1972)
The role of the human testis in the production of 17β-estradiol (E(2)) was investigated by determining the concentration of E(2) and testosterone in peripheral and spermatic vein plasma samples. Specimens were obtained from eight normal men, three men with hypogonadism, and two patients with the incomplete form of the feminizing testes syndrome. For comparison, similar studies were performed in four monkeys, 10 mongrel dogs, and 4 additional dogs who were given 1000 IU of human chorionic gonadotropin/day for 5 days. Plasma E(2) was measured by radioimmunoassay utilizing sheep anti-E(2) serum preceded by ether extraction and thin layer chromatographic separation of plasma steroids. Procedural blanks, which were subtracted from all reported values were 14.1±0.74 (SEM) pg for deionized water and 13.1±0.66 pg for charcoaladsorbed pooled male plasma. Pooled male and pooled female control plasmas averaged 17±0.71 pg/ml and 95±6.9 pg/ml, respectively; individual adult male specimens ranged between 8 and 28 with a mean of 18±1.4 pg/ml. In the eight normal men, the mean peripheral vein E(2) concentration was 20±1.6 pg/ml, while the spermatic vein concentration was 50 times as great, 1049±57 pg/ml. All three patients with testicular abnormalities had low spermatic vein E(2) concentrations (160, 280, and 416 pg/ml). Lesser E(2) gradients were found across the simian (3-fold) and canine (approximately 12-fold) testes. Testicular testosterone gradients (human 110-, simian 10-, and canine 77-fold) were greater than the E(2) gradients in all three species. In four dogs, HCG treatment elicited a 6-fold increase in peripheral and a 9-fold increase in spermatic vein testosterone concentrations; however, peripheral and spermatic vein E(2) concentrations did not differ from control values. Spermatic vein E(2) concentrations were > 4600 and 2210 pg/ml (post-HCG) in two patients with the incomplete form of the feminizing testes syndrome. Postorchiectomy, peripheral E(2) and testosterone concentrations fell precipitously in both patients, confirming the major contribution of the testes, in this syndrome, to circulating E(2) and testosterone. These studies provide direct evidence that the human testic secretes estradiol.